Bacterial diversity and production of sulfide in microcosms containing uncompacted bentonites. Issue 8 (August 2018) - Grigoryan, Alexander A.; Jalique, Daphne R.; Medihala, Prabhakara; Stroes-Gascoyne, Simcha; Wolfaardt, Gideon M.; McKelvie, Jennifer; Korber, Darren R.
Abstract: Aims: This study examined the diversity and sulfide-producing activity of microorganisms in microcosms containing commercial clay products ( e.g., MX-80, Canaprill and National Standard) similar to materials which are currently considered for use in the design specifications for deep geologic repositories (DGR) for spent nuclear fuel. Methods and results: In anoxic microcosms incubated for minimum of 60 days with 10 g l -1 NaCl, sulfide production varied with temperature, electron donor and bentonite type. Maximum specific sulfide production rates of 0.189 d −1, 0.549 d −1 and 0.157 d −1 occurred in lactate-fed MX-80, Canaprill and National Standard microcosms, respectively. In microcosms with 50 g l -1 NaCl, sulfide production was inhibited. Denaturing gradient gel electrophoresis (DGGE) profiling of microcosms revealed the presence of bacterial classes Clostridia, Bacilli, Gammaproteobacteria, Deltaproteobacteria, Actinobacteria, Sphingobacteriia and Erysipelotrichia . Spore-forming and non-spore-forming bacteria were confirmed in microcosms using high-throughput 16S rRNA gene sequencing. Sulfate-reducing bacteria of the genus Desulfosporosinus predominated in MX-80 microcosms; whereas, Desulfotomaculum and Desulfovibrio genera contributed to sulfate-reduction in National Standard and Canaprill microcosms. Conclusions: Commercial clays microcosms harbour a sparse bacterial population dominated by spore-forming microorganisms. Detected sulfate- and sulfur-reducing bacteria presumably contributed to sulfide accumulation in the different microcosm systems. Significance and impact of study: The use of carbon-supplemented, clay-in-water microcosms offered insights into the bacterial diversity present in as-received clays, along with the types of metabolic and sulfidogenic reactions that might occur in regions of a DGR ( e.g., interfaces between the bulk clay and host rock, cracks, fissures, etc. ) that fail to attain target parameters necessary to inhibit microbial growth and activity.